Mycobacterium w - a promising immunotherapeutic intervention for diseases - Stefan, Kirsten; Gordon, Ryan; Rolig, Annah; Honkala, Alexander; Tailor, Dhanir; Davis, Lara E.; Modi, Rajiv I.; Joshipura, Manjul; Khamar, Bakulesh; Malhotra, Sanjay V. (Frontiers in Immunology, 2024)
Immunomodulating agents interact with the immune system and alter the outcome of specific immune processes. As our understanding of the immune system continues to evolve, there is a growing effort to identify agents with immunomodulating applications to use therapeutically to treat various diseases. Mycobacterium w (Mw), a heat-killed mycobacterium, is an atypical mycobacterial species that possesses strong immunomodulatory properties. Mw was initially evaluated as an immune-therapeutic against leprosy, but since then Mw has generated a lot of interest and been studied for therapeutic applications across a host of diseases, such as pulmonary tuberculosis, tuberculous pericarditis, sepsis, lung cancer, and more. This article summarizes a large body of work published in the past five decades, describing various aspects of Mw and its potential for further therapeutic development.